Reflection of Bangladeshi cultural practices in Daily Sun’s magazines: morning tea, hood and ghroove - Hossain, Afrin Binte (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.